“Hollywood is no place for idealists”: Hollywood as Dystopia in Cinema and Fiction - Tomasz Fisiak (Zagadnienia Rodzajów Literackich)
The following article deals with the representation of Hollywood as a dystopian place, for women in particular, where glamour is a utopian façade for both literal and figurative corruption, where the lifespan of an actress is severely limited and the process of discarding “useless” artists is systemically implemented. My main point of reference will be Donald Wolfe’s 1970 Savage Intruder, one of the lesser known hag horrors. Moreover, I will allude to other films exploring a similar motif, not to mention Angela Carter’s 1977 novel entitled The Passion of New Eve, which also analyzes the falseness of Hollywood and its capacity for dystopia.